An overview of traumatic reticulopericarditis in cattle and buffaloes - Macedo, Gustavo Gomes [UNESP]; Ferreira, Lucas Vinícius de Oliveira [UNESP]; Chiacchio, Simone Biagio [UNESP] (My University, 2021)
Traumatic reticulopericarditis occurs due to the ingestion of foreign bodies that penetrate the reticulum towards the diaphragm and then the pericardium, resulting in traumatic pericarditis. It is a common disorder in cattle and buffalo, especially in developing countries associated with high economic losses and animal welfare. Indiscriminate eating habits and the mechanization of food are predisposing factors. The most common clinical signs are tachycardia, distention of the jugular veins, muffled heart sounds and submandibular, brisket and ventral edema. However, they are present in several pathologies, making early diagnosis difficult. Anemia, hyperfibrinogenemia, leukocytosis, neutrophilia, elevation of serum levels of the enzymes aspartate aminotransferase (AST), gamma glutamyl transferase (GGT), lactate dehydrogenase (LDH), serum bilirubin, creatine kinase (CK), hyperproteinemia, hypoalbuminemia and cytological analysis of cavity effusions with the presence of inflammatory cells are common laboratory findings. Radiography can identify foreign bodies, however inflammatory reactions and the presence of fibrinous exudates make it difficult to visualize. Ultrasonography and echocardiography, assist in the detection and characterization of effusions and the association of these tools with the assessment of cardiac biomarkers, are considered useful methods for making an early diagnosis. The prognosis is unfavorable and treatment is generally unsatisfactory, and proper management of this disorder is essential to prevent major losses. Therefore, the objective of the present review was to highlight the current progress of the disease in cattle and buffaloes due to its importance in animal production and health.
Keywords: Bubalus bubalis; Buffaloes; Cattle; Foreign body; Pericarditis; Traumatic